Paul Rolland e a consciência corporal no ensino de violino nos anos iniciais - Estrela, Iannara Farias Xavier (2024)
In instrumental practice, the movements of the body fulfill the essential function of performing the music written on the score by means of an instrument. Understanding the awareness of these body movements can improve the use of our study time, as well as our performance as teachers. The process of choosing methodological approaches for postural teaching is extremely important for instrument teachers, especially in the early years. We found in the methodology proposed by Paul Rolland (1911 - 1978) an approach to body awareness in violin teaching through which we believe it is possible to obtain positive results. The main objective of this research is to analyze the methodology proposed by Rolland in his manual The Teaching of Action in String Playing, one of his main publications. We started with a bibliographical survey, where we discussed the concept of body awareness based in different authors, in musical performance (LAGE et al, 2002; PEDERIVA, 2004; TEIXEIRA et al, 2015; LEONIDO et al, 2017) and violin performance (GAMA, 2016; FONSECA, 2011; KOTHE et al, 2011), especially Rolland (2007). Afterward, we present a summary of the Action Studies described by Rolland in his book The Teaching of Action in String Playing, followed by an analysis of his teaching proposal and a presentation of the main references that Rolland used to develop his methodology. We also show the similarities found between the Actions proposed by Rolland and Psychomotricity (YING, 2012; LOURO, 2019). Concluding with the contextualization by suggesting the utilization of this method in violin classes that use the collective teaching approach, based on a questionnaire carried out with eight teachers from the city of João Pessoa.